A New Conceptualization of the Conscience - Schalkwijk, Frans (Frontiers in Psychology, 2018)
With the transition from a one-person psychology of instinctual needs to a two-person psychology of relational needs, the metapsychological focus tends to shift from instinct theory to emotion motivation and systems theory, and, accordingly, familiar concepts have to be rethought. In this article, the superego is reconceptualised as a psychic regulation system for self-evaluation, comprising the capacity for empathy, the proneness to experience self-conscious emotions such as shame, pride, and guilt, and the capacity for moral reasoning. This new conceptualisation provides useful tools for addressing the actual functioning of the conscience in clinical psychoanalysis. Affective neuropsychoanalysis can make important contributions to this rethinking of the superego. It also brings clinical practice and psychoanalytic metapsychology closer to empirical research beyond the scope of clinical psychoanalysis. The new model offers ample opportunities for integrating affective neuroscience into the functioning of the conscience.